Synthesis and characterization of lime derived solid base catalyst for transesterification reaction - Pua F.-L.; Fauzan N.A.; Nasir M.A.M.; Othman R.; Jaafar S.N.S.; Subramaniam K. (American Institute of Physics Inc., 2023)
This study was focused to utilize the local lime resources and synthesis the new heterogeneous base catalyst from different types of lime products (Quicklime; Hydrated lime; Carbide lime) via calcination reaction. The structural, morphological, and elemental properties of the catalyst were examined through the use of X-ray diffraction (XRD), scanning electron microscope (SEM), and electron dispersive X-ray spectroscopy (EDX) analyses. The results showed calcium oxide (CaO) with 2.42 to 3.04 nm crystallite size was derived from lime products. Catalytic performance was evaluated through transesterification of palm oils. Fourier Transform Infra-red (FTIR) analysis results confirmed the presence of methyl ester after transesterification reaction. 2019 Author(s).